Pengaruh Pemberian Dosis Pupuk Kalium Nitrat dan Magnesium Sulfate Terhadap Hasil Tanaman Jeruk Siam (Citrus nobilis var. Microcarpa L.) - I Ketut Suda Armawan; Ni Komang Alit Astiari; Ni putu Anom Sulistiawati (Fakultas Pertanian, Universitas Warmadewa, 2023)
The purpose of this study was to determine the effect of doses of potassium nitrate and magnesium sulfate on the production of Siamese orange (Citrus Nobilis Var. Microcarpa L.) and their interactions, which was carried out in Bayung Gede Village, Kintamani District, Bangli Regency from December 2021 to July 2022. This study used a Randomized Block Design (RAK) with 2 factors arranged in a factorial manner. The first factor that was tried was the dose of potassium nitrate (K) fertilizer which consisted of 4 levels, namely: K0 (0 g/tree), K1 (250 g/tree), K2 (500 g/tree) and K3 (750 g/tree). . . While the second factor was the dose of magnesium sulfate (M) fertilizer which consisted of 4 levels, namely: M0 (0 g/tree), M1 (5 g/tree), M2 (10 g/tree) and M3 (15 g/tree). Thus, there were 16 treatment combinations, each given 3 times, so 48 citrus trees were needed. The results showed that the interaction of potassium nitrate fertilizer dose with magnesium sulfate (KxM) fertilizer did not significantly affect all observed variables. The highest fruit weight per tree was obtained at a dose of potassium nitrate fertilizer of 750 g/tree, which was 11.53 kg, an increase of 96.75% when compared to without potassium nitrate fertilizer which was only 5.86 kg. While the magnesium sulfate fertilizer treatment obtained the highest harvested fruit weight per tree at a dose of 15 g/tree, namely 10.17 kg, an increase of 30.05% when compared to magnesium sulfate fertilizer which was only 7.82 kg.